Taking back the streets : women, youth, and direct democracy - Kaplan, Temma, 1942- (University of California Press, 2004)
Toward the end of the twentieth century in places ranging from Latin America and the Caribbean to Europe, the United States, South Africa, Nigeria, Iran, Japan, China, and South Asia, women and young people took to the streets to fight injustices they believed they could not confront in any other way.